2010
DOI: 10.2355/isijinternational.50.476
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Transpassive Intergranular Corrosion Resistance of 304 Austenitic Stainless Steel by Thermomechanical Processing for Twin-induced Grain Boundary Engineering

Abstract: Grain boundary engineering (GBE) primarily aims to prevent the initiation and propagation of intergranular degradation along grain boundaries by frequent introduction of coincidence site lattice (CSL) boundaries into the grain boundary networks in materials. It has been reported that GBE is effective to prevent passive intergranular corrosion such as sensitization of austenitic stainless steels, but the effect of GBE on transpassive corrosion has not been clarified. In the present study, a twin-induced GBE uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Moreover, the impact of twinning on DRX and microstructure evolution in ASS at a high strain rate has also been reported in earlier studies [17]. In addition, the CSL boundaries are found to be effective in preventing passive intergranular corrosion [70], improving the resistance of grain coarsening [71], reducing the propagation rate of fatigue crack [72], increasing ductility and uniform elongation [73].…”
Section: The Role Of Twin On Drxmentioning
confidence: 55%
“…Moreover, the impact of twinning on DRX and microstructure evolution in ASS at a high strain rate has also been reported in earlier studies [17]. In addition, the CSL boundaries are found to be effective in preventing passive intergranular corrosion [70], improving the resistance of grain coarsening [71], reducing the propagation rate of fatigue crack [72], increasing ductility and uniform elongation [73].…”
Section: The Role Of Twin On Drxmentioning
confidence: 55%
“…38 The suppression of transpassive intergranular corrosion by GBE could be also explained by the disruption of the connectivity of random boundaries, at which phosphate and/or phosphorus segregate(s) preferentially, by CSL boundaries with a lower concentration of segregant. 18 intergranular chromium carbide precipitation and corrosion than random boundaries in 304 austenitic stainless steel. [6][7][8] This suggests that GBE has a high potential to inhibit the weld decay caused for a short time exposure to the sensitisation temperature range in welding thermal cycles.…”
Section: Effect Of Gbe On Intergranular Corrosionmentioning
confidence: 99%
“…37 A Coriou test 37 of 304 austenitic stainless steels containing different concentrations of phosphorus has shown that GBE is also effective to suppress the transpassive intergranular corrosion. 18 In passive corrosion, a well distributed CSL boundaries in the grain boundary network create a discontinuous chain of chromium depletion and can arrest the percolation of intergranular corrosion from the surface. 14 An analytical transmission electron microscopic observation has demonstrated that the chromium depletion at a CSL segment introduced by twin emission into a random boundary was significantly suppressed compared with that of the original random boundary during sensitisation.…”
Section: Effect Of Gbe On Intergranular Corrosionmentioning
confidence: 99%
See 2 more Smart Citations